The Effect of Educational Intervention Based on the Health Belief Model on Oral and Dental Health Behavior in Pregnant Women - Sahar Nickbin Poshtamsary; Abdolhosein Emami Sigaroudi; Rabiollah Farmanbar; Golpar Radafshar; Zahra Atrkar Roushan (Guilan University of Medical Sciences, 2020)
Introduction: The World Health Organization recognizes oral health as an integral part of public health and believes that untreated oral diseases may greatly affect the quality of life, especially in pregnant mothers who should maintain their health and their babies' health. Objective: This study aimed to determine the effect of educational intervention based on a health belief model on oral and dental health behavior in pregnant women. Materials and Methods: In this randomized clinical trial, 110 pregnant mothers attending 15 health centers in Rasht City, Iran (a total of 33 centers) were randomly allocated to case and control groups. After the analysis of pretest data (collected using a psychometric questionnaire), an intervention was designed and executed based on the Health Belief Model (HBM). Post-test was administered three months after the intervention and the obtained data were analyzed by using the Chi-square and independent and linear regression test. Results: The majority of the mothers in the case (83.6%) and control (89.1%) groups were 18- 30 years old and most mothers in the case (45.5%) and control (58.2%) groups had high school education. The Mean±SD score of awareness, different constructs of HBM, and performance increased significantly in the case group after the intervention (P<0.05). The Mean±SD score of performance was 35.45±12.52 in the case group before the intervention and it increased to 77.26±9.33 three months after the intervention (P<0.05). Conclusion: The results showed that intervention based on this model enhanced oral and dental health behaviors. The results also suggested that the mothers lacked adequate awareness and had a poor performance in adopting oral and dental health behaviors. This model can be used as a framework for designing and implementing educational interventions to decrease dental caries